Interaksi Sosial Masyarakat Umat Beragama dalam Mewujudkan Solidaritas Sosial di Kelurahan Bukit Nenas Kecamatan Bukit Kapur Kota Dumai - Meylisa Hutagalung; Maringan Sinambela; Masniar Hernawaty Sitorus; Martua Sihaloho; Jupalman Welly Simbolon (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
The background of this research related to Social Interaction is defined as a dynamic mutual social relationship, which concerns the relationship between individuals, individuals and groups, groups and groups. The main problem in this study is to understand the interaction of religious people in increasing solidarity between religious communities in Bukit Nenas Village by looking at the many positive activities carried out in the Bukit Nenas Village area. Cooperation carried out by religious communities is Islam, Protestant Christianity, Catholicism, Buddhism, and Hinduism. Especially when Muslims are performing worship during the holidays, people who live close to the mosque environment voluntarily help maintain security around the place of worship and who maintain that security from other Protestant and Catholic Christians. To see the benefits of the formation of a sense of solidarity between others, the researcher is interested in further studying the benefits of community interaction and its influence in realizing social solidarity in Bukit Nenas Village. The results of this study show that the influence of community interaction on socio-religious life in the village is very numerous, including from the social side, establishing good communication between communities, both communities around the house and communities that are far away and different environments, realizing and increasing community solidarity, and maintaining brotherhood. The benefit from the religious side is that harmony that has been maintained to this day can be used as an example by many people and other regions. Judging from the culture of interaction between communities that have cultural differences, the community knows about other cultures.